Design and Analysis of Grouting Pressure in Slurry Pipe Jacking Based on the Surrounding Soil Stability Mechanical Characteristics. (16th June 2022) - Liu, Jimin; Cheng, Hua; Cai, Haibing; Wang, Xuesong
Abstract : In slurry pipe jacking, lubricant slurry is commonly used to sustain against the displacement and pressure of the overcut area and reduce the interface friction of pipelines. Therefore, a reasonable grouting pressure should ensure the stability of surrounding soils, which is raised as a new method in this study. Not only ensure the grouting pressure is not too small to support the stratum effectively and reduce the frictional resistance but also ensure that the grouting pressure will not be too large to produce excessive deformation and affect the surrounding environment. First of all, the influence of grouting pressure on the stability of surrounding soil is analyzed, and the mechanical model of slurry grouting expansion is established. Then, the minimum grouting pressure is designed from the critical balance between radial expansion tension by grouting and loose earth pressure by jacking excavation, and the maximum grouting pressure is designed from the critical expansion pressure caused by grouting splitting. Finally, the rationality of grouting pressure design is proved by the engineering example of a slurry pipe-jacking project near Haikou Meilan Airport and on-site GPR detection test. All these work aims to raise a new theoretical solution of grouting pressure and provide theoretical reference for similar projects.